Evaluating the Vermont State police's PEACE model training program: phase 1. Issue 1 (2nd January 2022) - Fallon, Laura; Snook, Brent; Barron, Todd; Baker, Angela; Notte, Mike; Stephenson, Jeff; Trottier, Dan
ABSTRACT: The current study is the first phase of a larger evaluation of the Vermont State Police (VSP) PEACE Model interview training program. This evaluation measures the impact of the program on trainees' interviewing knowledge and attitudes, and opinions about the program. VSP Members participating in Tier 1 ( N = 72) and Tier 2 ( N = 46) PEACE interview training completed a questionnaire, both before and after training, about (1) their knowledge of interviewing and related concepts, (2) their attitudes about various interviewing practices, and (3) their beliefs about the training session. Results showed that training had a large effect on knowledge for participants in both training courses. As well, a majority of Tier 1 and Tier 2 trainees reported attitudes in line with scientific consensus after training. Specifically, most items related to eyewitness testimony, memory, and coercion were endorsed post-training by the majority of officers, while items covering deception detection and interrogation rights were endorsed less frequently. Additionally, trainees reported that their training experience was quite positive. Implications for the program and future directions for training are discussed.